2017
DOI: 10.1038/nrn.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Adult hippocampal neurogenesis and cognitive flexibility — linking memory and mood

Abstract: Adult hippocampal neurogenesis has been implicated in cognitive processes, such as pattern separation, and in the behavioural effects of stress and antidepressants. Young adult-born neurons have been shown to inhibit the overall activity of the dentate gyrus by recruiting local interneurons, which may result in sparse contextual representations and improved pattern separation. We propose that neurogenesis-mediated inhibition also reduces memory interference and enables reversal learning both in neutral situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
652
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 811 publications
(697 citation statements)
references
References 193 publications
18
652
0
5
Order By: Relevance
“…Neurogenesis is a biological process beginning from neural stem cells to mature neuron formation. This process is necessary for the development of the nervous system to ensure proper cognitive functions, such as behavior, mood, memory , and brain plasticity .…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenesis is a biological process beginning from neural stem cells to mature neuron formation. This process is necessary for the development of the nervous system to ensure proper cognitive functions, such as behavior, mood, memory , and brain plasticity .…”
Section: Discussionmentioning
confidence: 99%
“…Though unexpected, other studies have also shown varying degrees of sexual dimorphism in hippocampal structure and function (Cushman et al 2012; Galea 2008; Luine et al 2017). While the DNTP radial-arm maze task has been shown to be both hippocampal- and neurogenesis-dependent, conflicting views exist on whether it can properly assess pattern separation processes (Anacker and Hen 2017; Besnard and Sahay 2016; Clelland et al 2009; Santoro 2013), or more broadly spatial discrimination or other hippocampal functions. However, the fact that sexual dimorphism disappears in this assessment when the α7 nAChR is removed remains interesting.…”
Section: Discussionmentioning
confidence: 99%
“…The CA4 region, also known as the hilus, receives inputs from the granule cells of the dentate gyrus (Amaral, 1978) and major excitatory input from the cortex. The dentate gyrus plays a vital role in neurogenesis (Aimone, Deng, & Gage, 2014), and is linked with memory formation (Anacker & Hen, 2017 We performed a whole-brain connectome analysis using NBS and DTI to identify altered connections and networks and volumetric analysis of the hippocampal subfields to determine changes associated with vitamin D deficiency. The dentate gyrus plays a vital role in neurogenesis (Aimone, Deng, & Gage, 2014), and is linked with memory formation (Anacker & Hen, 2017 We performed a whole-brain connectome analysis using NBS and DTI to identify altered connections and networks and volumetric analysis of the hippocampal subfields to determine changes associated with vitamin D deficiency.…”
Section: Hippocampal Volume Loss Is Associated With Disrupted Netwomentioning
confidence: 99%